The Study of The Varanus Komodoensis Venom - Yan, Junzhe (Transactions on Environment, Energy and Earth Sciences, 2024)
As a very ancient and mysterious species, Varanus komodoensis is the world’s largest monitor lizard, the world’s largest living lizard, and the last descendant of the Australian biota, his mystery makes scholars all over the world want to uncover its mysterious veil. This article studies exactly what he is most famous for, namely the authenticity of his venom and the way it hunts. This article examines the many aspects known about it, including its venom, its drool, and the truth about its hunting methods. And concluded that its method of hunting was relatively simple and crude, using its strong torso function to maximize the lethality of its strong jaw and strong tail, quickly stunning and killing its prey, instead of using what people used to think. To hunt with virus-filled saliva or venom-filled glands. The main purpose of this study is to provide a better understanding of what is Komodo dragon. To enrich its image in the eyes of the people. And to dispel some timeless misconceptions, that they are very mysterious and fascinating creatures, that deserve protection and numbers are not many that they need help even more.